Impacts and challenges in oil palm cultivation and downstream applications of biomass - Wong, Mui Yun (Nova Science Publishers, 2018)
This book covers topics related to impacts and challenges in the oil palm production chain (with sustainability in mind) and consists of nine chapters. Three chapters deal with the upstream aspect, including a holistic approach in the sustainability analysis of oil palm processing; sustainable pest and disease management; and assessment on the impacts of oil palm plantations on butterfly fauna. Six chapters discuss downstream applications, including innovative pre-treatment methods and extraction mechanisms in crude palm oil (CPO) processing; challenges and potential of palm-based biomass and palm oil mill effluent for the production of sustainable power and value-added products; and innovative ways for extracting oil palm empty fruit bunch (EFB) lignin for nutraceutical and health supplements; reproducibility of natural resources for the synthesis of low transition temperature mixtures (LTTMS) as biomass pre-treatment; and reusing oil palm biomass waste to reinforce composite materials. Combining the expertise of leading researchers in their respective field, the book provides an overview on the impacts and challenges encountered in the sustainable oil palm production chain and offers a valuable reference work.